NEW DEVELOPMENTS OF OAO «BELNIILIT» IN THE FIELD OF CENTRIFUGAL CASTING - D. A. Volkov; A. P. Melnikov; A. D. Volkov; A. V. Mitskevich; R. E. Trubitskij (Литьë и металлургия)
New developments of OAO «BELNIILIT» in the field of centrifugal molding are given.